Phytolith Analysis as a Palaeoecological Tool for Reconstructing Mid-to Late-Pleistocene Environments in the Olorgesailie Basin, Kenya - Kinyanjui, Rahab (Department of Environmental and Geographical Science, 2024)
Olorgesailie Basin is an important prehistoric locus and holds a prominent place in African Quaternary research. It is located in the southern Kenya rift system (1˚ 35´S and 36˚ 27´E) and has preserved numerous archaeological findings of the Acheulean, Sangoan and Middle Stone Age occupations and most importantly, hominin cranium associated with the Acheulean hand axes. Evidence of past vegetation has hitherto been scarce, because the arid / semi-arid conditions are not conducive for preservation of organic plant microfossils. Phytolith analysis is used to reconstruct the vegetation history and understand hominin habitat preference during mid-late Pleistocene (~746-64 ka). A localised modern phytolith analogue is used to interpret the fossil assemblage. Descriptive analysis identified fifty nine phytolith morphotypes which were categorised into three major groups; grass short-cell phytolith, epidermal silicified appendages and sedge phytoliths. The identification and classification was based on the International Code for Phytolith Nomenclature and other existing literature. In order to determine the significance of the identified morphotypes in interpreting fossil data, two multivariate statistical analyses were performed on the database; Correspondence analysis distinguished vegetation components according to a moisture gradient while Cluster analysis identified unique morphotypes that were taxonomically affiliated to their parent plant species. However, the analyses were not able to distinguish plants along the altitudinal gradient. Fossil phytoliths derived from sixty palaeosol samples extracted from eight geological sections in three localities of the Olorgesailie Basin, were identified and tallied to determine vegetation cover and how this changed both spatially and temporarily during the mid-late Pleistocene period. Fossil phytolith frequencies were plotted on TILIA diagrams against the available 40Ar/39Ar dates. Correspondence analysis identified three vegetation components; grasslands, woody & herbaceous and aquatic and identified moisture availability as the major underlying factor influencing the morphotype clusters on the ordination space. An additional cluster analysis of forty morphotypes derived from grasses confirmed the known taxonomic affiliation of major grass short-cell phytoliths to four grass subfamilies (saddle ovate- C3 Arundinoideae, bilobate concave- and convex- outer margin short shaft and quadralobate-C4 Panicoideae, saddles-C4 Chloridoideae and bilobates convex outer margin long shaft-C4 Aristidoideae). From the non-grass category, achene and papillae phytolith morphotypes were identified as belonging to the Cyperaceae.